Strengthening drug policy and practice through ethics engagement: an old challenge for a new harm reduction. - Irwin, Kevin S; Fry, Craig L (The International journal on drug policy, 2007)
Harm reduction proponents aim to identify and support policies and programmes that moderate or decrease the deleterious consequences of illicit drug use. While harm reduction is clearly a value-based response to drugs, for many, 'ethics' merely represent institutional research and professional practice regulations to be satisfied, subjective moral claims, or philosophy that is too abstract to offer tangible benefits in keeping with the pragmatism of harm reduction. In this paper we revisit the relationship between harm reduction and ethics, reframe ethics as a pragmatic concern for all of harm reduction, and argue that greater attention to the actual values and beliefs underpinning harm reduction can help to enhance policy, practice and research outcomes. Examples are given of early progress in this area to illustrate possible features of ethics engagement in harm reduction, and existing ethics materials are highlighted as suitable supporting resources for applied ethical decision-making in this field.
Keywords: Decision Making; Harm Reduction; Humans; Public Health Practice; Public Policy; Research; Street Drugs; Substance-Related Disorders